PLZF Expression during Colorectal Cancer Development and in Normal Colorectal Mucosa according to Body Size, as Marker of Colorectal Cancer Risk - Francesco Mariani; Paola Sena; Giulia Magnani; Stefano Mancini; Carla Palumbo; Maurizio Ponz de Leon; Luca Roncucci (The Scientific World Journal)
Promyelocytic leukemia zinc finger protein (PLZF) is a protein involved in various signaling, growth regulatory, and differentiation pathways, including development/function of some T cells. Here, we aimed at the detection of PLZF during colorectal carcinogenesis, using immunofluorescence, and at the evaluation of the colocalization of PLZF with CD2 and CD56 positive cells (T, γδ, NK, and NKT cells), using confocal-microscopy, along colorectal carcinogenesis, since its earliest stages, that is, dysplastic aberrant crypt foci (ACF). Furthermore, we analyzed PLZF in the normal colonic mucosa (NM) according to anthropometric parameters of the subject. NM exhibited strong CD56 fluorescent staining. This infiltration was lost in both ACF and colorectal carcinoma (CRC), while PLZF presence increased from NM to ACF and CRC. Strong association was found between CD56+ colonic mucosa cell infiltration and body mass index. Interestingly, an increased stromal PLZF-reactivity was present in NM of obese subjects. This study shows that overexpression of PLZF and exclusion of NK cells in dysplastic microenvironment are very early events in the stepwise sequence leading to CRC and that lower levels of CD56+ cells in NM, together with increased levels of PLZF+ cells, can be a reflection of colon cancer risk due to obesity.